Identification of Soluble Mediators in IgG-Mediated Anaphylaxis via Fcγ Receptor: A Meta-Analysis - Kow, Audrey Siew Foong; Chik, Azirah; Soo, Kuan-Meng; Khoo, Leng Wei; Abas, Faridah; Tham, Chau Ling (Frontiers in Immunology, 2019)
Background: Anaphylaxis is an acute and life-threatening allergic response. Classically and most commonly, it can be mediated by the crosslinking of allergens to immunoglobulin E (IgE)- high affinity IgE receptor (FcεRI) complex found mostly on mast cells. However, there is another pathway of anaphylaxis that is less well-studied. This pathway known as the alternative pathway is mediated by IgG and its Fc gamma receptor (Fcγ). Though it was not documented in human anaphylaxis, a few studies have found that IgG-mediated anaphylaxis can happen as demonstrated in rodent models of anaphylaxis. In these studies, a variety of soluble mediators were being evaluated and they differ from each study which causes confusion in the suitability, and reliability of choice of soluble mediators to be analyzed for diagnosis or therapeutic purposes. Hence, the objective of this meta-analysis is to identify the potential soluble mediators that are involved in an IgG-mediated anaphylaxis reaction. Methods: Studies related to IgG-mediated anaphylaxis were sourced from five search engines namely PubMed, Scopus, Ovid, Cochrane Library, and Center for Agricultural Bioscience International (CABI) regardless of publication year. Relevant studies were then reviewed based on specific inclusion factors. The means and standard deviations of each soluble mediator studied were then extracted using ImageJ or Get Data Graph Digitiser software and the data were subjected to meta-analysis. Results: From our findings, we found that histamine, serotonin, platelet activating factor (PAF), β-hexosaminidase, leukotriene C4 (LTC4), mucosal mast cell protease-1 (MMCP-1), interleukins (IL)-4,−6, and−13; tumor necrosis factor alpha (TNF-α), and macrophage inflammatory protein-1α (MIP-1α) were often being analyzed. Out of these soluble mediators, histamine, PAF, β-hexosaminidase, IL-6, and−13, MIP-1α and TNF-α were more significant with positive effect size and p < 0.001. As study effect was relatively small, we performed publication bias and found that there was publication bias and this could be due to the small sample size studied. Conclusion: As such, we proposed that through meta-analysis, the potential soluble mediators involved in rodent IgG-mediated anaphylaxis to be histamine, PAF, β-hexosaminidase, IL-6 and−13 and MIP-1α, and TNF-α but will require further studies with larger sample size.